Radiation-associated angiosarcoma of the breast: radical resection technique of the entire radiation field - Johannes Tobias Thiel; Michael Bauer; Adrien Daigeler; Vladyslav Kavaka; Jonas Kolbenschlag; Dominik Steiner; Anna Storz; Sebastian Hoffmann (Therapeutic Advances in Medical Oncology)
Background: Radiation-associated angiosarcoma of the breast (RAASB) is a rare secondary angiosarcoma that typically develops subsequent to breast-conserving therapy for breast cancer. The parameters of the resection width and depth remain the subject of considerable controversy. More recent data indicate that radical resection of the complete radiation field at the thorax is associated with improved local control and survival. Objectives: The present study investigates the radical resection technique of the entire radiation field and subsequent defect coverage in RAASB, as well as the medium-term follow-up. Design: Monocentric, retrospective, and non-comparative study. Methods: From January 2017 to January 2024 a total of 10 patients with RAASB were treated at our hospital. The radical resection technique was employed in the treatment of all patients, encompassing the entire radiation field. Three patients received local flaps (two of whom received vertical and transversal rectus abdominis muscle flaps and one received a local random pattern flap), while the remaining seven were treated with split-thickness skin grafts for defect coverage. Results: The median age at initial diagnosis of breast cancer was 59.3 ± 9.41 years, while that of RAASB was 66.2 ± 8.32 years. The median latency period between the start of irradiation of the chest wall and the initial presentation of RAASB was 6.5 ± 3.08 years. The cumulative median total radiation dose was 57.23 ± 8.34 Gray (cumulative Gray) in 9 of the 10 patients. The overall survival (OS) was 80% in the cohort, with a median follow-up period of 40.0 ± 27.96 months. Three patients exhibited local relapses following radical resection, with two of these patients ultimately succumbing to their condition. Conclusion: Patients with RAASB may benefit from a radical resection of the entire radiation field. Despite the relatively mutilating nature of the procedure, the radical resection technique may have the potential to reduce the rate of local recurrence and prolong OS.